Cognitive and behavioural inhibition deficits in neurodegenerative dementias (2020)
Disinhibition, mainly caused by damage in frontotemporal brain regions, is one of the major causes of caregiver distress in neurodegenerative dementias. Behavioural inhibition deficits are usually described as a loss of social conduct and impulsivity, whereas cognitive inhibition deficits refer to impairments in the suppression of prepotent verbal responses and resistance to distractor interference. In this review, we aim to discuss inhibition deficits in neurodegenerative dementias through behavioural, cognitive, neuroanatomical and neurophysiological exploration. We also discuss impulsivity and compulsivity behaviours as related to disinhibition. We will therefore describe different tests available to assess both behavioural and cognitive disinhibition and summarise different manifestations of disinhibition across several neurodegenerative diseases (behavioural variant of frontotemporal dementia, Alzheimer’s disease, Parkinson’s disease, progressive supranuclear palsy, Huntington’s disease). Finally, we will present the latest findings about structural, metabolic, functional, neurophysiological and also neuropathological correlates of inhibition impairments. We will briefly conclude by mentioning some of the latest pharmacological treatment options available for disinhibition. Within this framework, we aim to highlight i) the current interests and limits of tests and questionnaires available to assess behavioural and cognitive inhibition in clinical practice and in clinical research; ii) the interpretation of impulsivity and compulsivity within the spectrum of inhibition deficits; and iii) the brain regions and networks involved in such behaviours.